Assessment of the fear of Delivery among Women at Labor - ali, Rabea (Iraqi National Journal of Nursing Specialties, 2007)
Objective: To assess the fear of laboring women regarding the delivery on themselves and theirnewborns.Methodology : A descriptive study was conducted on (100) pregnant women who where admitted tolabor room in Al- Yarmock Teaching Hospital/Maternity Units, Fatima Al- Zahra and Ibn-Al BaladiMaternity and Pediatric Hospital. The questionnaire was consisted of pregnant womensocio-demographic data, reproductive data and fear items of labor. Data were collected by using aquestionnaire format, through interview technique and reviewing pregnant records, descriptive andinferential statistical procedure were used to analyze the data.Results: The main results of the study revealed a high mean of scores with moderate (RS) in women'sfear regarding labor on her self ( labor difficulties ,dying during labor, labor pain related to uterinecontractions, prolonged labor, fear of being left alone, fear of episiotomy, and exposure to infection )And on their newborn in (delivery of unhealthy or abnormal newborn ,newborn death during or afterdelivery, head dystocia, fetal asphyxia, and exposure to cold and infection ). The findings alsopresented significant differences between women's fear regarding labor on themselves and sociodemographic and reproductive variables in (age, education, residency, socioeconomic status, history ofabortion, pregnancy &delivery complications ), and on their newborn in (age, education, type of family.gravidity, parity, history of abortion, &pregnancy complications).Recommendation: Educational program can be designed to orient the pregnant women towardphysiological and psychological changes during pregnancy, labor & delivery process and Initiation ofprenatal education classes in primary health care centers.